Canine Geriatric Rehabilitation: Considerations and Strategies for Assessment, Functional Scoring, and Follow Up - Frye, Christopher; Carr, Brittany Jean; Lenfest, Margret; Miller, Allison (Frontiers in Veterinary Science, 2022)
Geriatric animals account for half of the pet population in the United States with their numbers increasing annually. Furthermore, a significant percentage of veterinary patients with movement limitations could be grossly categorized as geriatric and living within the end stage of their predicted lifespans. Because mobility is correlated to quality of life and time to death in aging dogs, a major goal in optimizing canine geriatric health is to improve functional movement. Within the geriatric population, identifying disabilities that affect daily living and quality of life may be used by the rehabilitation practitioner to provide stronger prognoses, treatment goals, and outcome measures. Examples of such means are described within this review. In human medicine, the concept of “optimal aging”, or “healthy aging”, has emerged in which inevitable detrimental age-related changes can be minimized or avoided at various levels of physical, mental, emotional, and social health. Both environment and genetics may influence aging. Identifying and improving environmental variables we can control remain a key component in optimizing aging. Furthermore, diagnosing and treating age related comorbidities common to older populations allows for improved quality of life and is often directly or indirectly affecting mobility. Obesity, sarcopenia, and a sedentary lifestyle are a trifecta of age-related morbidity common to both people and dogs. Healthy lifestyle choices including good nutrition and targeted exercise play key roles in reducing this morbidity and improving aging. Disablement models act as essential tools for creating more effective physiotherapy plans in an effort to counter dysfunction and disability. Within these models, functional testing represents a standard and validated means of scoring human geriatric function as well as monitoring response to therapy. Because of the great need in dogs, this review aims to provide a reasonable and testable standardized framework for canine functional scoring. We believe a complete assessment of canine geriatric patients should comprise of identifying environmental variables contributing to health status; diagnosing comorbidities related to disease and aging; and characterizing disability with standardized methods. Only through this process can we construct a comprehensive, reasonable, and targeted rehabilitation plan with appropriate follow up aimed at healthy aging.